2002
DOI: 10.1161/01.cir.0000038365.78031.9c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase Is Activated in Subjects at Risk of Developing Type 2 Diabetes and Is Associated With Impaired Vascular Reactivity

Abstract: Background-We have previously shown that endothelial function is impaired not only in diabetes but also in subjects at risk of developing type 2 diabetes. We hypothesized that changes in the expression or activity of the endothelial isoform of nitric oxide synthase (eNOS), the receptor for advanced glycation end products (RAGE), and poly(ADP-ribose) polymerase (PARP) are related to this impairment. Methods and Results-We included a control group of 21 healthy subjects, a group of 22 healthy individuals with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
132
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 39 publications
11
132
2
1
Order By: Relevance
“…For example, PARP activation has been shown to be present in healthy subjects at risk of developing diabetes, as well as in established type 2 diabetics. 23 PARP-1 inhibitors have also been shown to alleviate symptoms of diabetic complications. [24][25][26] Furthermore, PARP-deficient mice are protected from streptozotocininduced diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PARP activation has been shown to be present in healthy subjects at risk of developing diabetes, as well as in established type 2 diabetics. 23 PARP-1 inhibitors have also been shown to alleviate symptoms of diabetic complications. [24][25][26] Furthermore, PARP-deficient mice are protected from streptozotocininduced diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, overactivation of PARP represents an important mechanism of tissue damage in various pathological conditions associated with oxidative and nitrosative stress, including myocardial reperfusion injury (Zingarelli et al 1998), heart transplantation , heart failure (Pacher et al 2002b, c), stroke (Eliasson et al 1997), circulatory shock (Szabó et al 1997a, Oliver et al 1999, Jagtap et al 2002, Shimoda et al 2003, and autoimmune beta-cell destruction associated with diabetes mellitus (Burkart et al 1999, Pieper et al 1999. Activation of PARP and beneficial effects of various PARP inhibitors have been demonstrated in various forms of endothelial dysfunction such as the one associated with circulatory shock, hypertension, atherosclerosis, preeclampsia and aging (Szabó et al 1997, Hung et al 2002, Martinet et al 2002.…”
Section: Poly(adp-ribose) Polymerase and Its Activationmentioning
confidence: 99%
“…Activation of PARP and beneficial effects of various PARP inhibitors have been demonstrated in various forms of endothelial dysfunction such as the one associated with circulatory shock, hypertension, atherosclerosis, preeclampsia and aging (Szabó et al 1997, Hung et al 2002, Martinet et al 2002. Furthermore, recent data suggest that activation of PARP importantly contributes to the development of endothelial dysfunction in various experimental models of diabetes and also in humans (Garcia Soriano et al 2001, Soriano et al 2001a, Pacher et al 2002d, Szabó et al 2002b). In addition, it has recently been demonstrated that PARP activation plays a pathogenetic role in diabetic nephropathy, neuropathy and retinopathy , Minchenko et al 2003, Li et al 2004.…”
Section: Poly(adp-ribose) Polymerase and Its Activationmentioning
confidence: 99%
“…Increased PARP activity can be measured in skin biopsies not only in patients with type 2 diabetes but also in healthy people with a parental history of type 2 diabetes (i.e. those with a higher risk of developing the disease) [30]. The prolonged PARP activation in GDM patients may be involved in the development of carbohydrate intolerance in later life or in the development of late cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%